Diet in irritable bowel syndrome: What to recommend, not what to forbid to patients - Cozma-Petruţ, Anamaria; Loghin, Felicia; Miere, Doina; Dumitraşcu, Dan Lucian (World journal of gastroenterology : WJG, 2017)
A substantial proportion of patients with irritable bowel syndrome (IBS) associate their symptoms with the ingestion of specific foods. Therefore, in recent years, scientific research has increasingly focused on the role of diet in IBS and dietary management is now considered an important tool in IBS treatment. This article reviews the main dietary approaches in IBS emphasizing evidence from experimental and observational studies and summarizing the main diet and lifestyle recommendations provided by dietary guidelines and scientific literature. Despite the limited evidence for a beneficial role, general advice on healthy eating and lifestyle is recommended as the first-line approach in the dietary management of IBS. Standard recommendations include adhering to a regular meal pattern, reducing intake of insoluble fibers, alcohol, caffeine, spicy foods, and fat, as well as performing regular physical activity and ensuring a good hydration. Second-line dietary approach should be considered where IBS symptoms persist and recommendations include following a low FODMAP diet, to be delivered only by a healthcare professional with expertise in dietary management. The efficacy of this diet is supported by a growing body of evidence. In contrast, the role of lactose or gluten dietary restriction in the treatment of IBS remains subject to ongoing research with a lack of high-quality evidence. Likewise, further clinical trials are needed to conclude the efficacy of probiotics on IBS symptoms.